A chronic toxicity test for the tropical marine snail Nassarius dorsatus to assess the toxicity of copper, aluminium, gallium, and molybdenum. (20th April 2016) - Trenfield, Melanie A.; van Dam, Joost W.; Harford, Andrew J.; Parry, David; Streten, Claire; Gibb, Karen; van Dam, Rick A.
Abstract: Chronic toxicity test methods for assessing the toxicity of contaminants to tropical marine organisms are generally lacking. A 96‐h chronic growth rate toxicity test was developed for the larval stage of the tropical dogwhelk, Nassarius dorsatus . Growth rates of N. dorsatus larvae were assessed following exposures to copper (Cu), aluminium (Al), gallium (Ga), and molybdenum (Mo). Exposure to Cu at 28 °C validated the sensitivity of the test method, with 10% (EC10) and 50% (EC50) effect concentrations of 4.2 μg/L and 7.3 μg/L Cu, respectively. The EC10 and EC50 values for Al (<0.45‐μm filtered fraction) at 28 °C were 115 μg/L and 185 μg/L, respectively. The toxicity of Cu and Al was also assessed at 24 °C and 31 °C, representing average year‐round water temperatures for subtropical and tropical Australian coastal environments. At 24 °C, the growth rate of control larvae was reduced by 52% compared with the growth rate at 28 °C and there was an increase in sensitivity to Cu (EC50 = 4.7 μg/L) but a similar sensitivity to Al (EC50 = 180 μg/L). At 31 °C the control growth rate increased by 35% from that measured at 28 °C and there was reduced sensitivity to both Cu and Al (EC50s = 8.5 μg/L and 642 μg/L, respectively). There was minimal toxicity resulting from Ga (EC50 = 4560 μg/L) and Mo (no effect at ≤7000 μg/L Mo). Environ Toxicol Chem 2016;35:1788–1795. © 2015 SETAC